Pembuatan Brondong dari Berbagai Beras - B.A. Susila Santosa; Narta Narta; D.S. Damardjati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
A technology of puffed-salted rice processing has been studied. Five rice varieties (IR 64, IR 42, IR 48, Cisadane and Gemar) were used. Salt solution was sprayed onto the rice prior to puffing, at level of 10 % of rice weight. Puffed salted rice were compared to puffed unsalted-rice. The results showed that either rice varieties or salting affected the puffed rice characteristics. Puffed rice of Gemar variety had the highest whiteness and volume expansion, and lowest hardness. Protein quality decreased in the puffed rice, indicated by decreasing in amino acids composition. Aromatics and S-amino acid were more susceptible to degradation during puffing than the others. Salt spraying before puffing resulted in puffed rice with lower whiteness and volume expansion, and higher water solubility and gel consistency. Salting also increased amino acids susceptibility to degradation during puffing. Salting, however, decreased in the ability to absorb water and increased hardness, therefore the treatment would keep puffed rice crispy for longer lime rather than puffed, unsalted-rice. Organoleptics evaluation also showed that puffed rice of Gemar variety had the high score of color, appearance, taste and crispiness, though poor in flavor. Rice salting decreased in the panelist acceptability of color and appearance, but increased in the crispiness, taste and flavor acceptability.